Necessary constraints: Samuel R. Delany on science fiction. - Samuelson, David N. (Review of Contemporary Fiction)
Focuses on the critical writings of Samuel R. Delany on science fiction. Works focusing on science fiction criticism and theory; Personal background of Delany; Details of how he became interested in science fiction; Delany's views on science fiction; Issues discussed in his writings.